THE IMPORTANCE OF ACADEMIC SCRIPT IN THE STATUTES FORMATTING TO REALIZE ASPIRASIONAL AND RESPONSIVE LAW - Abdul Basyir (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
This study aims to identify and assess the importance of an academic paper on the laws formation in creating aspirations and responsive law and also to knowing the implications of law that is not accompanied by an academic paper. This type of research is normative research. The approach used to address this fundamental problem,  namely the statute approach and conceptual approach. Academic Paper in the formation of legislation is as early  draft legislation and regulation,  institutionalize or formalize conditions and/or events in the community into legislation. Creating aspirations and responsive law is because the law is formed starting from the bottom to the top (bottom up),  and the product of legislation can be enforced and accepted by the community. The implications of the draft legislation that is not accompanied by an academic paper that is denied to be discussed,  unprocedural,  and the legislation products can be constrained when executed or enforced.Keywords: academic paper,  The formation of legislation,  implication.Abstrak